Silent Diplomacy: Wendat Boys’ “Adoptions” at the Jesuit Seminary, 1636–1642 - JACKSON, VICTORIA (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
In 1636, the Jesuits opened an all-boys seminary school for Wendat children just outside of Quebec. The Jesuits hoped to use the school as a tool of conversion, with the expectation that students would then return home to Wendake to bring others to the Catholic faith. While the Wendat agreed to send a few of their children to the school, their goal was to facilitate a friendly relationship between the Wendat and the French. This diplomacy was conducted through the lens of adoption. While at the seminary, the boys engaged with their French educators: they seemed to convert to Catholicism and they adapted their behaviour to match French expectations, as if they had been adopted by their Jesuit instructors. However, upon leaving the school, many reverted to more traditional Wendat practices, indicating their acculturation was a temporary, but practical, means of affiliating themselves with their Jesuit allies. Individual stories from three students are highlighted to illustrate the significance of the youths’ agency, adaptability, and use of kinship relationships to facilitate a diplomatic bond with some of the early French settlers.